Functional characteristics of plant growth-promoting rhizobacteria from Acacia mangium L. - Zakry, Fitri Ab Aziz; Azhar, Syafira Azreen; Malahubban, Masnindah; Mohammad Yusoff, Martini (Journal of Phytology, 2025)
Nodulation, a pivotal developmental process in nitrogen-fixing plant-microbe associations, was investigated in Acacia mangium. This study aimed to isolate and characterise root nodule bacteria for plant growth-promoting traits. Ten bacterial isolates underwent screening, revealing similar morphologies and growth rates. All isolates exhibited positive indole acetic acid production, while PI1A and PI2A demonstrated phosphorus and potassium solubilisation. Four isolates, namely PI1A, PI2A, PI3A, and PDG1A, showed positive nitrogen fixation. PI1A emerged as the most promising strain, significantly enhancing (p<0.05) mung bean seedling root fresh weight at 210.37±5.22 mg and root dry weight at 112.67±3.28 mg as compared to the control at 139.27±5.71 mg and 65.40±3.70 mg, respectively. Based on fatty acid analysis, isolate PI1A was identified as belonging to the species Photorhabdus luminescens. In conclusion, P. luminescens isolate PI1A exhibits significant potential candidate in a biofertiliser and bio-stimulant formulation for sustainable agriculture.